Hand Hygiene and Antimicrobial Resistance in the COVID-19 Era: An Observational Study - Antonino Russotto; Edoardo Rolfini; Giovanni Paladini; Claudia Gastaldo; Costanza Vicentini; Carla Maria Zotti (MDPI AG, 2023)
Hand hygiene (HH) is one of the most important infection prevention and control strategies at the hospital level. The aim of this study was to evaluate the potential COVID-19 pandemic impact on HH practices and rate of healthcare-associated infections. Data on alcohol-based handrub consumption (AHC) and antimicrobial resistance across 27 Italian hospitals over the period 2017-2021 were considered. Data on Methicillin-resistant Staphylococcus aureus (MRSA) and carbapenem-resistant Enterobacteria (CRE) were extracted from the antimicrobial resistance regional surveillance system. A significant increase was highlighted, with a peak in 2020 and a partial fall in 2021 for AHC (p < 0.001). The decrease in MRSA rates in 2021 compared to 2017-2019 was significant (p = 0.013). A significant Spearman's correlation between AHC and CRE rates was found (Spearman's ρ −0.646, p = 0.032). This study supports the importance of AHC monitoring and showed that improving AHC was an attainable goal in the COVID-19 era. However, other strategies are needed to maintain the high levels of AHC attained during the pandemic, in order to avoid a progressive drop that has already begun in 2021. Furthermore, our results support the inverse relationship between AHC and infection rates and antimicrobial-resistant bacteria.